Leadership Influence on Occupational Health and Safety Management System: A Case Study of a Malaysian Dangerous Goods Warehouse Using Process Enneagram - Ang, Lim (2025)
Many potential dangers and pitfalls exist in the handling and storage of dangerous goods (DG) cargo. Regardless, many enterprising businessmen participate in the rapid proliferation of DG warehouses, some out of pragmatism and yet others, out of the necessity to provide much needed service in the overall DG supply chain. This study used Process Enneagram as the tool to understand the influence of leadership on OHS issues found in a DG warehouse which specializes in the handling, storage, and delivery of DG cargo, where any significant lapse in following standard operating procedures (SOP) may lead to incidents/accidents among their employees. This research used a qualitative case study approach, where data was collected from interviewing the participants of the selected Malaysian DG warehouse, observations of workers’ activities on site, artefacts and signages pertaining to OHS issues as well as from accessing relevant company documents pertinent to the research questions. Notable findings from the study include prevalent display of leadership by example from the leadership ranks, compassionate leadership and a deeply ingrained family oriented leadership style. Interestingly, this study also found that the top leadership actively spearheaded the drive towards OHS issues, contrary to the expected stance of pushing the finance and economic agenda. To some extent, this study has contributed to the continued application of Process Enneagram in the field of leadership research in the OHS context within a Malaysian DG warehouse. This research also holds the implication that it is definitely possible to operate a DG warehouse safely, supported by a capable team of leaders with the right priorities, and sustain it as a viable business concern.